Sternaspidae (Annelida, Sedentaria) from Vietnam with description of three new species and clarification of some morphological features - Zhadan, Anna E.; Tzetlin, Alexander B.; Salazar-Vallejo, Sergio I. (Zootaxa, 2017)
Five sternaspid species were found near Vietnam shores: Sternaspis britayevi sp. nov., S. costata von Marenzeller, 1879, S. nana sp. nov., S. papillosa sp. nov., and S. spinosa Sluiter 1882. Sternaspis britayevi is described from the shallow water in Vietnam inhabiting soft bottoms; it resembles S. spinosa described from Java and S. thorsoni Sendall & Salazar-Vallejo, 2013 described from the Persian Gulf, but differs in having a medially projected and markedly ribbed fan of the ventro-caudal shield and nearly parallel, distally widened and rounded branchial plates. Sternaspis nana sp. nov. is described from Nha Trang Bay; it differs from the other known species by the combination of the following characters: small size, evenly distributed micropapillae and regular rows of long cirriform papillae; posterior chaetal fascicles consisting of single thick chaeta; a ventral shield with smooth integument, without ribs and usually without concentric lines. Sternaspis papillosa sp. nov. is also described from Nha Trang Bay; it resembles S. africana Augener, 1918 and S. andamanensis Sendall & Salazar-Vallejo, 2013 by having similar ventro-caudal shields but differs by body papillation and details of the ventro-caudal shield. Based upon observations of different species some morphological features are clarified: 1) notochaetae are present in introvert chaetigers as delicate capillaries; 2) peg-chaetae are really a dense group of more than 100 thin individual chaetae, embedded in a fibrous matrix, and covered by a common sheath; 3) the pharynx is an eversible, lobed, axial non-muscular proboscis with a ciliated surface; 4) the body cavity is divided by three septa in the anterior body region, and there are no other septa; and 5) an eversible anal peduncle is confirmed, as has been shown by early taxonomists.